ANALISIS PERUBAHAN PENGGUNAAN LAHAN PERTANIAN AKIBAT PEMBANGUNAN JALAN TOL BERBASIS CITRA SATELIT DI KABUPATEN LAMPUNG SELATAN - LINA MARLINA; Teguh Endaryanto; Astria Hijriani (Politeknik Negeri Lampung, 2021)
There are concerns that toll road construction will change livelihoods and reduce agricultural production. This study aims to map the potential agricultural land affected by toll road construction and to analyze the changes. The research was conducted from July to August 2020. The research site was in South Lampung Regency with the consideration that this area is one of the districts affected by toll road construction and is a center for food crops in Lampung Province. To see land changes carried out with a remote sensing system and then calculate the rate of land change. The rate of land conversion analyzed is in the period 2014 to 2020 in South Lampung Regency, with the assumption that in 2015, toll roads will be built and in 2020 the construction will be completed. The data source used is the 2014 and 2020 land use map of South Lampung Regency, the result of interpretation of Landsat imagery. The results showed that the toll road construction almost entirely took up agricultural potential land, both land used for plantations and food crops. From the total land area, 72.13 percent is plantation land and 25.12 percent is land planted with food crop commodities. Key words: agricultural production, conversion, satellite image, toll roads